ANALISIS KOMPETENSI PROPESIONAL MAHASISWA GEOGRAFI PROGRAM PENDIDIKAN PROFESI GURU GEOGRAFI (PPG) PRA JABATAN GELOMBANG 1 DAN 2 DI SMA KOTA PADANG TAHUN 2023 - Nurfajrina, Aisah; Ernawati, Ernawati (DEPARTEMEN GEOGRAFI FIS UNP, 2025)
Material, Structure, Concepts and Scientific Mentality that Support Subjects Domain Learning Achievements (CP), Learning Objectives (TP), Flow of Learning Objectives (ATP), Creative curriculum development, Professional development progress is carried out by conducting reflective research. Researchers just take for granted what is done in the form of a simple research report. The aim of descriptive research is to systematically present the facts and characteristics of an object or subsystem. Quantitative research methods are research methods that use positive bias to conduct research on a sample or population. Based on the analysis, the professional results of Vocational Teacher Education (PPG) students in waves 1 and 2 of training at Padang City High School in 2023 are around 84.2% in the Very Proficient category. Even though they are in the very mastery category, it is still important for PPG students to be aware of developing their abilities improve quality of the teaching and learning process and have high performance to the quality of education.